1994
DOI: 10.1104/pp.104.4.1385
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Signals from the Roots and Rapid Cell-Wall Hardening in Growing Maize (Zea mays L.) Leaves Are Primary Responses to Polyethylene Glycol-Induced Water Deficits

Abstract: We investigated mechanisms involved in inhibition of maize (Zea mays 1.) leaf-elongation growth following addition of nonpenetrating osmolyte to the root medium. l h e elongation rate of the first true leaf remained inhibited for 4 h after addition of polyethylene glycol 6000 (PEC; -0.5 MPa water potential), despite progressive osmotic adjustment in the growing leaf tissues. Thus, inhibition of leaf growth did not appear to be directly related to loss of leaf capacity to maintain osmotic potential gradients. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
1
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 153 publications
(101 citation statements)
references
References 27 publications
(46 reference statements)
1
98
1
1
Order By: Relevance
“…The reversible change in position gave a comparative measure of elasticity in the same units. Detailed characterizations of this method for measuring leaf extensibility in maize plants and a comparative review of its merits have been previously reported (Neumann 1993;Chazen & Neumann 1994;Chazen et al 1995;Neumann 1995). No attempt was made to redefine plasticity values in the terms of the Lockhart (1965) model equations.…”
Section: In Vivo Plasticitymentioning
confidence: 99%
See 4 more Smart Citations
“…The reversible change in position gave a comparative measure of elasticity in the same units. Detailed characterizations of this method for measuring leaf extensibility in maize plants and a comparative review of its merits have been previously reported (Neumann 1993;Chazen & Neumann 1994;Chazen et al 1995;Neumann 1995). No attempt was made to redefine plasticity values in the terms of the Lockhart (1965) model equations.…”
Section: In Vivo Plasticitymentioning
confidence: 99%
“…646, supplied by Galilee Seed Ltd, Israel) were germinated for 2 d and then grown hydroponically on 01 strength nutrient solution, or 1 mol m^' CaCU (for low-nutrient treatment), in an environmentally regulated growth chamber (16 h photoperiod, light intensity 35 W m""^ PAR at plant height, temperature 27 ± 2 °C), as previously described (Neumann 1993;Chazen & Neumann 1994;Chazen et al 1995). The leaves were assayed from the second day after transfer to hydroponic culture, i.e.…”
Section: Plant Growthmentioning
confidence: 99%
See 3 more Smart Citations